2011
DOI: 10.1371/journal.pcbi.1002155
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-cell, Multi-scale Model of Vertebrate Segmentation and Somite Formation

Abstract: Somitogenesis, the formation of the body's primary segmental structure common to all vertebrate development, requires coordination between biological mechanisms at several scales. Explaining how these mechanisms interact across scales and how events are coordinated in space and time is necessary for a complete understanding of somitogenesis and its evolutionary flexibility. So far, mechanisms of somitogenesis have been studied independently. To test the consistency, integrability and combined explanatory power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(139 citation statements)
references
References 84 publications
(225 reference statements)
3
135
0
1
Order By: Relevance
“…We have demonstrated that spatial signals (for instance stemming from a biochemical gradient) can be a direct and (based on the visual and kinematic comparison) effective manner of instructing morphogenesis. This has been shown for various other life forms like Arthropoda and Vertebrata [63], [47], [37]. Our simulations regarding the effectiveness of auxin as the primary signal controlling root growth show that based on local auxin production a stable auxin pattern can be produced, however this potentially a slow process.…”
Section: Discussionsupporting
confidence: 65%
“…We have demonstrated that spatial signals (for instance stemming from a biochemical gradient) can be a direct and (based on the visual and kinematic comparison) effective manner of instructing morphogenesis. This has been shown for various other life forms like Arthropoda and Vertebrata [63], [47], [37]. Our simulations regarding the effectiveness of auxin as the primary signal controlling root growth show that based on local auxin production a stable auxin pattern can be produced, however this potentially a slow process.…”
Section: Discussionsupporting
confidence: 65%
“…Experimental and modeling data have demonstrated that the sweeping wave of segmentation clock oscillations may not even be necessary for proper somite formation (Hester et al, 2010;Soza-Ried et al, 2014). Although initiation of somite patterning may occur in the posterior PSM, additional patterning mechanisms also operate later.…”
Section: Discussionmentioning
confidence: 99%
“…Some promising first results come from an in silico modeling platform: A novel multi-cellular agent-based model (ABMs) of vasculogenesis using the CompuCell3D (http://www.compucell3d.org/) modeling environment supplemented with semi-automatic knowledgebase creation has been developed by ePA. Dynamic cell ABMs have been shown to simulate complex developing systems and, consequently, display a potential to simulate adverse effects (Kleinstreuer et al, 2013;Hester et al, 2011;Shirinifard et al, 2013) and aberrant tissue fusion (Ray and Niswander, 2012).…”
Section: Fig 14: Roadmap To Animal-free Toxicokinetic Predictionsmentioning
confidence: 99%